PERAN KBIH MERESTORASI MENTAL JAMAAH HAJI MANDIRI: STUDI DI KOTA TANGERANG BANTEN - Muhammad Ishom (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
The role of the Hajj Guidance Group (KBIH) has not been effective as the implementation of the independent Hajj mentalty’s program, such as self-sustaining travel, Manasik-al-hajj, and health. That’s factor are; (1) there is trade orientation of trade orientation, (2) distinction between independent pilgrimage and group hajj (3) pilgrimage following the culture of patriarchi (3) prestice group.